2013
DOI: 10.5114/fn.2013.35952
|View full text |Cite
|
Sign up to set email alerts
|

Original article Heterogeneity of local tissue microenvironment influences differentiation of oligodendroglial progenitors

Abstract: JJo oa an nn na a S Sy yp pe ec ck ka a, , A An nn na a S Sa ar rn no ow ws sk ka a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…To study spinal cord pathology or reparative mechanisms, the experiments should preferably be looked upon in the context of the spinal cord microenvironment [ 6 , 17 – 19 ]. As we proved before [ 20 , 21 ] either the spinal cord or the brain environment exerts a markedly different influence on cultured cells. In order to prove this, transverse organotypic spinal slice cultures were established [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 60%
“…To study spinal cord pathology or reparative mechanisms, the experiments should preferably be looked upon in the context of the spinal cord microenvironment [ 6 , 17 – 19 ]. As we proved before [ 20 , 21 ] either the spinal cord or the brain environment exerts a markedly different influence on cultured cells. In order to prove this, transverse organotypic spinal slice cultures were established [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 60%
“…Their sensitivity makes them vulnerable to excitotoxic insults but OPCs are also susceptible to external manipulation for the purpose of favoring the desired regenerative processes. Moreover, their fate-choice and maturation was significantly modified in the vicinity of the spinal cord slices [78, 79]. The reports published by other groups revealed the region-specific multipotentiality of these glia-committed progenitors [80, 81].…”
Section: Discussionmentioning
confidence: 99%
“…Many lipid biosynthetic enzymes are regulated by mTORC1 and mTORC2 in other systems (Yecies et al, 2011;Ricoult and Manning, 2013), and the Wood laboratory has previously shown that there are a plethora of mTOR complex targets, including lipid enzymes, which are modulated upon pharmacological inhibition of mTOR in vitro (Tyler et al, 2011). There is increasing evidence for regional heterogeneity of oligodendrocytes (Reynolds and Herschkowitz, 1987;Hardy et al, 1996;Riddle et al, 2006;Sypecka and Sarnowska, 2013). For example, the ablation of Fyn kinase results in differential impact on myelination in different areas of the CNS (Sperber et al, 2001).…”
Section: Discussionmentioning
confidence: 99%